PENERAPAN KONSEP MANAJEMEN MUTU DALAM PENGEMBANGAN PENDIDIKAN ISLAM: PERSPEKTIF AL-QURAN DAN HADIST - salsabila, putri; wulandari, Sri wulandari; habib, syafaatul Habib; fison, Khrisfison (As-Sulthan Journal of Education, 2025)
Islamic education is one of the important pillars in the development of a dignified society. To achieve this goal, it is necessary to improve the quality of Islamic education on an ongoing basis. One approach that can be used to improve the quality of Islamic education is to apply the concept of quality management. Quality management is an approach that focuses on meeting customer needs and satisfaction. In the context of Islamic education, customers are students, parents, the community, and other stakeholders. The application of the concept of quality management in Islamic education aims to produce graduates who have competencies that are in accordance with customer needs and expectations. The application of the concept of quality management in Islamic education can be studied from the perspective of the Qur'an and hadith. In the Qur'an, there are various verses that instruct Muslims to always try to improve their self-quality, both in terms of science, morals, and skills. This shows that Islam highly values quality and quality.